Human Resource Practices in IT industry: An empirical research of Bengaluru city - Parvathi, A.; Venkadesh, Dr. D. (The journal of contemporary issues in business and government, 2022)
This research article aims to “To measure the impact of human resource practices determinants on employee performance in IT industry”. The paper applies data reduction using Exploratory Factor Analysis (EFA) on a sample of 312 respondents drawn from 6 IT companies in the Bangalore city and condenses a set of 22 statements converted into a five human resource practices determinants. The present study proposes a model of the impact of human resource practices determinants on employee performance. The study found that compensation, recruitment and selection, training & development, performance appraisal and promotion are impacting significantly the employee performance. Therefore, IT companies should focus on the above factors to enrich human resource practices determinants. The study investigated the impact of determinants of HR practices on employee performance in IT industry concluded that compensation had the highest impact on the employee performance followed by recruitment and selection, training & development, performance appraisal and promotion.